High temperature causes negative whole‐plant carbon balance under mild drought. Issue 2 (4th July 2013) - Zhao, Junbin; Hartmann, Henrik; Trumbore, Susan; Ziegler, Waldemar; Zhang, Yiping
Summary Theoretically, progressive drought can force trees into negative carbon (C) balance by reducing stomatal conductance to prevent water loss, which also decreases C assimilation. At higher temperatures, negative C balance should be initiated at higher soil moisture because of increased respiratory demand and earlier stomatal closure. Few data are available on how these theoretical relationships integrate over the whole plant. We exposed Thuja occidentalis to progressive drought under three temperature conditions (15, 25, and 35°C), and measured C and water fluxes using a whole‐tree chamber design. High transpiration rates at higher temperatures led to a rapid decline in soil moisture. During the progressive drought, soil moisture‐driven changes in photosynthesis had a greater impact on the whole‐plant C balance than respiration. The soil moisture content at which whole‐plant C balance became negative increased with temperature, mainly as a result of higher respiration rates and an earlier onset of stomatal closure under a warmer condition. Our results suggest that the effect of drought on whole‐plant C balance is highly temperature‐dependent. High temperature causes a negative C balance even under mild drought and may increase the risk of C starvation.